ANALISIS PENGARUH KONDISI KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP BUSINESS RISK (STUDI KASUS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Prasetyo, Hendro Adi; Triyono, Triyono (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2014)
Bank is a fi rm which collects funds from society in the deposit term and spread it in the credit term and or in the other tems to increase the standard living of society. Therefore, it is urgent to get peopleâs credibility, because the activities of the bank rely on that. The aim of this research is to analyse the fi nancial condition effect in proxcy with capital adequacy ratio (CAR), non performing loan (NPL), loan to deposit ratio (LDR), net interest margin (NIM), and fi rm size toward business risk measured by deviation standart from return on asset (ROA). The methods of this research are double regression analisys, proper model test, classic assumptions test, and hypothesis test. The source of data used in this research are the banks in Indonesia Stock Exchange registered in 2008-2012. The data are chosen by using purposive sampling method which bank reports the annual report and Indonesian Capital Market Directory (ICMD) . From those criteria, this research gets 111 banks. The result shows that capital adequacy ratio (CAR), non performing loan (NPL), and net interest margin (NIM) have the signifi cant infl uences toward business risk. While loan to deposit ratio (LDR) and fi rm size have no signifi cant infl uences to business risk.